The socio-economic impact of tourism on communities around the Pilanesberg National Park, North West Province, South Africa - Mochechela, Maria Mologade (University of Limpopo (Turfloop Campus), 2010)
The purpose of this study was to determine the socio-economic impact of tourism on communities around the tourist destinations and tourist attractions, with specific reference to the Pilanesberg National Park and the specific impact it has on the communities around it. Both qualitative and quantitative research methods were used and 252 respondents responded positively by filling in questionnaires. Interviews were conducted with the Pilanesberg National Park management. The research findings reveal that the communities around the Pilanesberg National Park, specifically Mogwase, Moruleng, Ledig and Mabele-a-pudi are benefiting from the National Park through employment. Findings also indicate that the National Park is contributing positively towards the local economy of the area and the development of the communities. At the same time, however, the research findings indicate that the national park is impacting negatively on the local communities by contributing to the increasing cost of services.
Thesis (M.Dev.) --University of Limpopo, 2010
Keywords: Tourism; 338.4791; Tourism -- South Africa; Economic development